Decreased consumption of natural rewards in rhesus monkeys with prolonged methamphetamine abstinence - Jiahui Zhou; Hang Su; Chengjie Tang; Xiaotian Wu; Zijing Wang; Wenlei Zhang; Rongwei Zhai; Haifeng Jiang (Frontiers in Psychiatry, 2024)
RationaleRelapse to drug use is a major clinical challenge in the treatment of addictive disorders, including psychostimulant use and may be exacerbated by reduced sensitivity to natural, non-drug reward. Given the relatively limited set of outcomes, and short withdrawal time in rodent studies, we conducted a more detailed assessment of the response to natural rewards in methamphetamine (METH) naive versus exposed monkeys during long-term abstinence.MethodsThis study introduced an improved sucrose preference test (iSPT) to assess natural reward seeking and consumption in monkeys with long-term abstinence after methamphetamine (METH) use. The test was administered to sixteen naive monkeys and five METH exposed monkeys that had been abstinent for at least 3 months.ResultsMETH exposed monkeys showed a lower sucrose preference score in both the iSPT (z = -2.10, p = 0.036) and the sucrose preference test (z = -2.61, p = 0.009). The sucrose preference score was significantly correlated with the latency of the establishment of stable sucrose-preference (r = -0.76, df = 46, p < 0.001) but not with the other variables. Furthermore, water-sucrose switch latency and switch times were significantly negatively correlated (r = -0.50, df = 20, p = 0.02).ConclusionThese results show reductions in natural reward consumption during long-term methamphetamine abstinence.